Deposition carrier for negative electrode zinc of alkaline nickel-zinc battery

By using the porous graphite film as zinc deposition carrier, the nucleation and growth mode of zinc are changed, the problems of zinc dendrites and hydrogen evolution side reactions are solved, and the safety and life of nickel-zinc batteries are improved.

CN120349117APending Publication Date: 2025-07-22HUNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510492287.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-18
Publication Date
2025-07-22

AI Technical Summary

Technical Problem

The prior art is difficult to effectively inhibit the growth of zinc dendrites and hydrogen evolution side reactions, resulting in the safety and life of nickel-zinc batteries, especially under the requirements of high surface capacity.

Method used

The porous graphite film is used as the deposition carrier of zinc, and the nucleation and growth mode of zinc are changed through physical domain confining action. The hydrogen evolution reaction is suppressed by the hydrophobicity of the graphite film, and zinc nucleation and growth in the pores of the graphite film.

Benefits of technology

Effectively inhibit the growth of zinc dendrites, improve the safety and cycle life of nickel-zinc batteries, reduce hydrogen evolution side reactions, and improve Coulomb efficiency and battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120349117A_ABST
    Figure CN120349117A_ABST
Patent Text Reader

Abstract

The invention provides a deposition carrier with a porous graphite film as alkaline nickel-zinc battery negative electrode zinc and a preparation method of the deposition carrier, and the preparation method comprises the following steps: S1, NaCl particles are subjected to ball milling, and NaCl powder with different particle sizes is obtained by adjusting the rotating speed of a ball mill; s2, uniformly mixing NaCl powder obtained by ball milling, graphite flakes and graphite powder according to a certain proportion, putting the mixture into N-methyl pyrrolidone (NMP), putting polyvinylidene fluoride (PVDF) according to a certain mass ratio, and continuously stirring; s3, the surface of a zinc sheet is coated with the solid-liquid mixture, the thickness of a coating film is regulated and controlled, and the zinc sheet is put into a vacuum drying oven to be dried for a certain time; and S4, soaking the dried film in water for a certain time, and drying to obtain the porous graphite film serving as the zinc deposition carrier. The porous graphite film provided by the invention has relatively good cycle performance as a deposition carrier of a zinc negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage and conversion materials, and particularly to a porous graphite film deposition carrier for negative electrode zinc of an aqueous alkaline nickel-zinc battery.

Background Art

[0002] An aqueous alkaline nickel-zinc battery is a green secondary battery using ZnO and β-Ni(OH)2 as negative and positive electrode materials respectively, and an aqueous KOH solution as the electrolyte, which has the advantages of high energy density, high discharge voltage, low cost and safety. The negative electrode material ZnO can dissolve in a strong alkaline solution and exists in the electrolyte in the form of soluble tetrahydroxozincate ion Zn(OH)4 2- . Therefore, during the charging process of the nickel-zinc battery, the nucleation and deposition of negative electrode zinc easily lead to the problem of zinc dendrite growth, and at the same time, a hydrogen evolution side reaction also occurs. The growth of zinc dendrites easily pierces the diaphragm, resulting in short circuit between the positive and negative electrodes of the battery, thus causing safety problems. The hydrogen evolution reaction consumes the electrolyte, reducing the efficiency and service life of the battery.

[0003] To solve the above problems, in the reported related methods and technologies, generally measures such as adding organic or inorganic additives to the electrolyte are currently used to inhibit the growth of zinc dendrites, reduce the hydrogen evolution side reaction, and improve the cycle life of the nickel-zinc battery. However, the above methods only play a certain inhibitory role in the growth of zinc dendrites and the hydrogen evolution side reaction, and cannot completely and effectively inhibit the growth of zinc dendrites. Especially when facing the high areal capacity requirement (>3 mAh / cm 2 ) of the nickel-zinc battery electrode in industrialization, many of the above reported improvement measures are difficult to meet.

[0004] Therefore, it is necessary to break the shackles of conventional ideas and methods, and develop and provide a method from a new perspective that can effectively inhibit the growth of zinc dendrites, improve the cycle life, and at the same time inhibit the hydrogen evolution side reaction, that is, the present invention uses a porous graphite film as a carrier for zinc deposition, changes the nucleation and growth mode of zinc through the physical confinement effect of the porous graphite film, deposits zinc within the pores of the graphite film, and uses the physical barrier effect of the graphite film to achieve the purpose of inhibiting the growth of zinc dendrites and improving the cycle life. At the same time, the strong hydrophobic property of the graphite material is used to inhibit the hydrogen evolution side reaction, thereby effectively improving the comprehensive electrochemical performance of the nickel-zinc battery.

Summary of the Invention

[0005] The object of the present invention is to overcome the above technical problems existing in the zinc negative electrode of the alkaline nickel-zinc battery for a long time, and provide a porous graphite film as a deposition carrier for negative electrode zinc, thereby improving the cycle life of the nickel-zinc battery and reducing the hydrogen evolution side reaction.

[0006] To achieve the above object, the present invention provides a porous graphite film as a deposition carrier for negative electrode zinc, and its preparation method includes the following steps:

[0007] S1: Ball-mill NaCl particles, and by adjusting the rotation speed of the ball mill, NaCl powders with different particle sizes are obtained;

[0008] S2: Mix the NaCl powder obtained by ball milling, graphite flakes and graphite powder evenly in a certain proportion, put the above mixture into N-methylpyrrolidone (NMP), and continuously stir in a certain mass ratio of polyvinylidene fluoride (PVDF);

[0009] S3: Coat the solid-liquid mixture on the surface of the zinc sheet, control the coating thickness, and put it into a vacuum drying oven to dry for a certain time;

[0010] S4: After soaking the dried film in water for a certain time and drying, a porous graphite film as a zinc deposition carrier is obtained.

[0011] Preferably, the mass ratio of the graphite flakes, graphite powder and NaCl is 1:1:(0.5 - 2).

[0012] Preferably, the addition amount of polyvinylidene fluoride in step S2 is 5% - 15% of the sum of the masses of the graphite powder and graphite flakes.

[0013] Preferably, the drying temperature in step S3 is 80°C - 120°C.

[0014] Compared with the related technology, in the technical solution provided by the present invention, a porous graphite film is used to replace the zinc sheet as the deposition carrier for negative electrode zinc in an alkaline nickel-zinc battery, and the following beneficial effects are obtained:

[0015] (1) Compared with the zinc sheet, the graphite material has more stable chemical properties, stronger hydrophobicity and lower hydrogen evolution potential. Therefore, the graphite film as a zinc deposition carrier can inhibit the hydrogen evolution side reaction of the nickel-zinc battery, improve the coulombic efficiency and enhance the cycle life;

[0016] (2) As a zinc deposition carrier, the porous graphite film enables zinc to nucleate and grow in the pores of the graphite film, thus avoiding the zinc dendrites that are likely to appear when using a zinc sheet as the deposition carrier, improving the safety of the nickel-zinc battery, because zinc dendrites can pierce the battery separator, causing short circuit between the positive and negative electrodes and thus triggering safety accidents;

[0017] (3) When the porous graphite film is used as a zinc deposition carrier, the cycle life of the nickel-zinc battery is greatly improved compared with that when the zinc sheet is used as the deposition carrier, demonstrating the superiority of the porous graphite film carrier.

Description of the Drawings

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention, the following will briefly introduce the accompanying drawings required for the description of the embodiments. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other accompanying drawings can be obtained based on these drawings, where:

[0019] Figure 1 (a) When a zinc sheet and a porous graphite film are used as deposition carriers in Embodiment 1, the charge-discharge cycle performance diagram of an alkaline nickel-zinc battery at a zinc deposition areal capacity of 1.5 mAh / cm 2 and a current density of 40 mA / cm 2 conditions;

[0020] Figure 1 (b) is a top view of a scanning electron microscope (SEM) of the porous graphite film before zinc deposition;

[0021] Figure 1 (c) is a cross-sectional SEM diagram of the porous graphite film after zinc deposition;

[0022] Figure 1 (d) and (e) are respectively the elemental distribution diagrams of zinc and carbon corresponding to Figure 1 (c);

[0023] Figure 2 (a) and (b) are respectively the wetting angle photos of the electrolyte used in the experiment and the graphite sheet and zinc sheet;

[0024] Figure 2 (c) is the linear sweep voltammetry (LSV) hydrogen evolution curve of the graphite film and the zinc sheet;

[0025] Figure 3 When the graphite film prepared in Embodiment 2 is used as a zinc deposition carrier, at a zinc deposition areal capacity of 1.5 mAh / cm 2 and a current density of 40 mA / cm 2 conditions, the cycle performance diagram;

[0026] Figure 4 When the graphite film prepared in Embodiment 3 is used as a zinc deposition carrier, at a zinc deposition areal capacity of 1.5 mAh / cm 2 and a current density of 40 mA / cm 2 conditions, the cycle performance diagram.

Detailed implementation manners

[0027] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts belong to the scope of protection of the present invention.

[0028] The present invention provides a preparation scheme of a porous graphite film as a deposition carrier for zinc, including the following steps:

[0029] S1: Ball-mill NaCl particles, and obtain NaCl powders with different particle sizes by adjusting the rotation speed of the ball mill.

[0030] S2: Mix the ball-milled NaCl powder, graphite flakes and graphite powder evenly in a certain proportion, put the above mixture into N-methylpyrrolidone (NMP), and continuously stir in a certain mass ratio of polyvinylidene fluoride (PVDF).

[0031] S3: Coat the solid-liquid mixture on the surface of the zinc sheet, control the coating thickness, and put it into a vacuum drying oven to dry for a certain time.

[0032] S4: After soaking the dried film in water for a certain time and drying, obtain a porous graphite film as a zinc deposition carrier.

[0033] Preferably, the mass ratio of the graphite flakes, graphite powder and NaCl is 1:1:(0.5 - 2).

[0034] Preferably, the addition amount of polyvinylidene fluoride in step S2 is 5% - 15% of the sum of the masses of the graphite powder and graphite flakes.

[0035] Preferably, the drying temperature in step S3 is 80°C - 120°C.

[0036] The porous graphite film provided by the present invention as a zinc deposition carrier is prepared by the above method.

[0037] Example 1

[0038] Mix the ball-milled graphite flakes, graphite powder and NaCl evenly in a mass ratio of 1:1:1, put the above mixture into N-methylpyrrolidone (NMP), and put 10% of polyvinylidene fluoride (PVDF) of the sum of the masses of the graphite powder and graphite flakes, and continuously stir. Coat the stirred solid-liquid mixture on the surface of the zinc sheet, and put it into a vacuum drying oven to dry at 120°C for 10 hours. Subsequently, soak the dried film in water for 6 hours, and after soaking and drying again, obtain a porous graphite film as a zinc deposition carrier.

[0039] Figure 1 (a) When a zinc sheet and a porous graphite film are used as deposition carriers respectively, the charge-discharge cycle performance diagram of an alkaline nickel-zinc battery when the surface capacity of zinc deposition is 1.5 mAh / cm 2 and the current density is 40 mA / cm 2 is shown. Among them, the number of cycles with the commonly used zinc sheet as the deposition carrier is 910 times, while under the same test conditions, the number of cycles with the graphite film as the deposition carrier reaches 2,500 times, showing a substantial improvement compared with the zinc sheet carrier, fully demonstrating the superiority of the porous graphite film as a zinc deposition carrier. Figure 1 (b) is the top view of the scanning electron microscope (SEM) of the graphite film before zinc deposition, and the porous structure can be clearly seen. Figure 1 (c) is the cross-sectional SEM image of the graphite film after zinc deposition, and Figure 1 (d) and (e) are the elemental distribution maps of zinc and carbon respectively. From these three images, it can be seen that zinc is deposited inside the porous graphite film serving as the carrier, inhibiting the growth of zinc dendrites, achieving the purpose of the present invention, and the charge-discharge cycle performance has been greatly improved.

[0040] Figure 2 (a) and (b) are the test photos of the wetting angle of the electrolyte used in the experiment on the surfaces of the graphite sheet and the zinc sheet respectively. Among them, the wetting angle of the electrolyte on the graphite surface is 140°, while on the zinc sheet surface it is 104°, which indicates that the graphite sheet has stronger hydrophobicity compared with the zinc sheet. Figure 2 (c) is the linear sweep voltammetry (LSV) curve of the graphite film and the zinc sheet, that is, the hydrogen evolution curve. At a current density of 10 mAh / cm 2 , the hydrogen evolution potential of the graphite film is reduced by 60 mV compared with the zinc sheet. This shows that compared with the zinc sheet carrier commonly used in nickel-zinc batteries, the porous graphite film carrier in the present invention has a lower hydrogen evolution potential, that is, the porous graphite film has a stronger ability to inhibit the hydrogen evolution reaction compared with the zinc sheet, thereby reducing the hydrogen evolution side reaction and improving the cycle life of the nickel-zinc battery.

[0041] Example Two

[0042] The graphite flakes, graphite powder and NaCl obtained by ball milling are mixed evenly according to the mass ratio of 1:1:0.5. The above mixture is put into N-methylpyrrolidone (NMP), and 5% of polyvinylidene fluoride (PVDF) based on the sum of the masses of the graphite powder and graphite flakes is added, and continuous stirring is carried out. The stirred solid-liquid mixture is coated on the surface of the zinc sheet and put into a vacuum drying oven to dry at 100 °C for 10 hours. Subsequently, the dried film is soaked in water for 6 hours. After soaking and drying again, a porous graphite film serving as a zinc deposition carrier is obtained.

[0043] Figure 3When the prepared graphite film is used as the deposition carrier of zinc, at a zinc deposition areal capacity of 1.5 mAh / cm 2 and a current density of 40 mA / cm 2 The cycling performance graph under the conditions shows that its cycle life reaches 1500 times, which is a significant improvement compared to 910 cycles of the zinc sheet as the carrier under the same test conditions, demonstrating the superiority of the porous graphite film as the deposition carrier of zinc.

[0044] Example 3

[0045] The graphite flakes, graphite powder and NaCl obtained by ball milling were mixed evenly in a mass ratio of 1:1:2. The above mixture was put into N-methylpyrrolidone (NMP), and 15% of polyvinylidene fluoride (PVDF) based on the sum of the masses of graphite powder and graphite flakes was added, and continuous stirring was carried out. The stirred solid-liquid mixture was coated on the surface of the zinc sheet and placed in a vacuum drying oven at 80 °C for 10 hours. Subsequently, the dried film was soaked in water for 6 hours, and after soaking and drying again, a porous graphite film as the zinc deposition carrier was obtained.

[0046] Figure 4 When the prepared graphite film is used as the deposition carrier of zinc, at a zinc deposition areal capacity of 1.5 mAh / cm 2 and a current density of 40 mA / cm 2 The cycling performance graph under the conditions shows that its cycle life reaches 1750 times, which is a significant improvement compared to 910 cycles of the zinc sheet as the carrier under the same test conditions, demonstrating the superiority of the porous graphite film as the deposition carrier of zinc.

[0047] Compared with the related technologies, in the technical solution provided by the present invention, a porous graphite film is used to replace the zinc sheet as the deposition carrier of the negative electrode zinc in the alkaline nickel-zinc battery, and the following beneficial effects are obtained:

[0048] (1) Compared with the zinc sheet, the graphite material has more stable chemical properties, stronger hydrophobicity and lower hydrogen evolution potential. Therefore, the graphite film as the deposition carrier of zinc can inhibit the hydrogen evolution reaction of the nickel-zinc battery, improve the coulombic efficiency and increase the cycle life;

[0049] (2) When the porous graphite film is used as the deposition carrier of zinc, zinc nucleates and grows in the pores of the graphite film, thus avoiding the zinc dendrites that are likely to appear when using the zinc sheet as the deposition carrier, improving the safety of the nickel-zinc battery, because the zinc dendrites can pierce the battery separator, causing the positive and negative electrodes to short-circuit, thus triggering safety accidents;

[0050] (3) When the porous graphite film is used as the deposition carrier of zinc, the cycle life of the nickel-zinc battery has been significantly improved compared to using the zinc sheet as the deposition carrier, proving the superiority of the porous graphite film carrier.

[0051] The above are only the embodiments of the present invention. It should be noted here that for those of ordinary skill in the art, improvements can be made without departing from the inventive concept of the present invention, but these all fall within the protection scope of the present invention.

Claims

1. Application of a porous graphite film as a deposition carrier of zinc for the negative electrode of an alkaline nickel-zinc battery, characterized in that, The porous graphite film is composed of graphite material, with NaCl powder as the pore-forming agent, and is prepared through the following steps: S1: Ball-mill the NaCl particles, and by adjusting the rotation speed of the ball mill, obtain NaCl powders with different particle sizes; S2: Mix the NaCl powder obtained by ball milling, graphite flakes and graphite powder evenly in a certain proportion, put the above mixture into N-methylpyrrolidone (NMP), and continuously stir in a certain mass ratio of polyvinylidene fluoride (PVDF); S3: Coat the solid-liquid mixture on the surface of the zinc sheet, control the film thickness, and put it into a vacuum drying oven to dry for a certain period of time; S4: After soaking the dried film in water for a certain period of time and then drying, obtain the porous graphite film as the zinc deposition carrier; the mass ratio of the graphite flakes, graphite powder and NaCl is 1:1:(0.5 - 2).

2. The application according to claim 1, characterized in that, The addition amount of polyvinylidene fluoride in step S2 is 5% - 15% of the sum of the masses of the graphite powder and graphite flakes.

3. The application according to claim 1, wherein The drying temperature in step S3 is 80°C - 120°C.